Tradisi Peta Kapanca Pernikahan di Kabupaten Bima; Perspektif Imam Syafi’i - Idharulhaq Idharulhaq; Hamzah Hasan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab dan Hukum, 2021)
The aimed of this research are 1) To know the practice in implementation and the meaning of Peta Kapanca's tradition In Wedding In Simpasai Village Lambu Subdistrict Bima Regency. 2) To know the view of Imam Syafi'i to the implementation of Peta Kapanca's tradition in Wedding In Simpasai Village Lambu Subdistrict Bima Regency. The Kings of this research is qualitative descriptive research by using Teologi Normatif (Syar'i) approachment and fenomenology. The sources of  this research data are the  figure of religion, the figure of society, the future of  custom and Zikir Kapanca's Team. The method of data collect are Observation, Interview and documentation. The technique of data processing are data reduction, data presentation and conclusion. The results of this research are the implementation of Zikir and Peta Kapanca in Simpasai Village Lambu Subdistrict Bima Regency beginning with greetings, istighfar, syahadat, shalawat and read  another ayat of holy Quran. Inai's leaf patch. The bridge sit on the place with the hands positions are straight. Banana's leaf and the bridge's foot straight. The bridge patch Inai's leaf until seven times. Yellow rice sow patch on the bridge by read shalawat of prophet Mohammad. The view of Imam Syafi'i to this tradition is not contadiction with Him caused this tradition accomodations the syariah and the values of Islam as His fiqih that meaning : custom can be consideration of law. Therefore, Zikip Peta Kapanca's Tradition of Simpasai Village can be eternal based on Imam Syafi'i's Perspective  in consider of Islam Law. The implication of this research are 1. Hopefully to all the society of Bima Regency and especially for Simpasai Village for maintain this culture that develop in our society Especially Zikir peta Kapanca. 2 Zikir peta Kapanca's culture is legacy of our Grandmother in Kingdom time, throughout needed the caring of our  government, the figure of religion, the figure of custom, the figure of society, Young generation, and also the researcher.Keywords : Wedding, Kapanca Map, Imam Syafi’i